Notifiche
Cancella tutti

Integrale definito

  

0
152

Risolvere senza la tecnica X SOSTITUZIONE!

Autore
1 Risposta



2

∫((x^2 - 1)·e^x) dx=

=∫(x^2·e^x) dx - ∫(e^x) dx =

=x^2·e^x - 2·∫(x·e^x) dx - ∫(e^x) dx =

=x^2·e^x - 2·(x·e^x - ∫(e^x) dx - ∫(e^x) dx =

=x^2·e^x - 2·(x·e^x - e^x) - ∫(e^x) dx =

=(x^2 - 2·x + 2)·e^x - e^x =

=e^x·(x^2 - 2·x + 1)

Valutato in x=2:

e^2·(2^2 - 2·2 + 1) = e^2

Valutato in x=0:

e^0·(0^2 - 2·0 + 1) = 1

Risultato : e^2 - 1

 



Risposta
SOS Matematica

4.6
SCARICA